1981
DOI: 10.1016/s0022-5347(17)54881-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of High Grade Transitional Cell Cancer of the Upper Urinary Tract

Abstract: A total of 175 patients was operated on for grade 2, 3 or 4 transitional cell epithelioma of the upper urinary tract. Followup was between 5 and 26 years. The operations involved total nephroureterectomy, simple nephrectomy and local resection. Patient survival correlated well with tumor stage and, particularly, with tumor grade, and, consistently, was inferior to that of an age and sex-matched control group. The correlation of survival and ipsilateral tumor recurrence with the type of operation suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
3
5

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(82 citation statements)
references
References 18 publications
4
70
3
5
Order By: Relevance
“…Grade and stage are closely related, and the vast majority of World Health Organization Grade 1 (of 3) urothelial carcinomas are noninvasive, whereas the majority of higher grade tumors show invasion into the lamina propria or muscle layer (7). Previous studies at the Mayo Clinic showed that survival in patients with low-grade urothelial cancers of the upper urinary tract is identical to age-matched controls (20), whereas survival of patients with higher grade tumors correlated with advanced stage and was sig- All data are n. nificantly lower than patients with low-grade tumors and control patients (21,22). In our study, there was no difference in cancer-specific survival between patients with renal pelvic and ureteral cancers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Grade and stage are closely related, and the vast majority of World Health Organization Grade 1 (of 3) urothelial carcinomas are noninvasive, whereas the majority of higher grade tumors show invasion into the lamina propria or muscle layer (7). Previous studies at the Mayo Clinic showed that survival in patients with low-grade urothelial cancers of the upper urinary tract is identical to age-matched controls (20), whereas survival of patients with higher grade tumors correlated with advanced stage and was sig- All data are n. nificantly lower than patients with low-grade tumors and control patients (21,22). In our study, there was no difference in cancer-specific survival between patients with renal pelvic and ureteral cancers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In 60% of cases, nephrectomy without ureterectomy was performed and average survival was 6 months (17,18). Renal UC has a propensity to recur in the ipsilateral ureter at a rate of 30 to 40% and mandates radical nephroureterectomy (19,20). In one of our patients, with the presumed diagnosis of RCC, the ureter was left in situ.…”
Section: Commentsmentioning
confidence: 87%
“…These different microscopic differentiation should be mentioned in the report, as it has prognostic significance. (1,2,8,9) In urinary bladder, chronic nonspecific cystitis is the most common non-neoplastic lesion seen. It has other variants like xanthogranulomatous types, Granulomatous cystitis, metaplastic changes and malakoplakia (2,3) are also noted.…”
Section: Discussionmentioning
confidence: 99%
“…(8,9,10) Cystitis is the commonest non-neoplastic lesion. These diseases are more disabling than lethal.…”
mentioning
confidence: 99%